When microbes meet: Decay and microbial spirituality in the post-human art market - Lyn, Amanda (Anthropology of consciousness, 2023)
The future of art is dirt and decomposing shit. A deconstructed intestinal sea of microorganisms, spread out into the soil they were released back into following the extinction of their complex vessel. The genetic information they exchanged with each other as well as with their container, now existing in a vague memory, perhaps a feeling of sadness and longing, as they digest the once cherished artifacts of their human predecessors.